Effects of processing conditions on the mechanical and water absorption properties of resin transfer moulded kenaf fibre reinforced polyester composite laminates. - Rassmann, S.; Reid, R.G.; Paskaramoorthy, S. (Elsevier, 2010)
This paper focuses on the mechanical and water absorption properties of kenaf fibre reinforced polyester laminates manufactured by resin transfer moulding. Varying processing conditions were considered as alternatives to fibre treatments, thereby potentially avoiding additional cost and complexity in the manufacturing process. Laminates were produced by altering fibre moisture content, mould temperature and mould pressure following injection. Tensile, flexural, impact and water absorption tests were conducted. Processing conditions were found to have little effect on properties except for pressurisation which increased tensile and flexural strength and decreased water absorption at low fibre volume fractions. Examinations using a scanning electron microscope showed that all the laminates failed by fibre pull-out.
Keywords: Kenaf fibre; Fibre/matrix bond; Mechanical testing; Resin transfer moulding; RTM; Manufacturing process; Mould temperature; Thermal properties; Fibre volume fraction